Knowing isn’t doing: a behavior change perspective on chronic pain management - Janet R. Bezner (Frontiers in Public Health, 2026)
Chronic pain management increasingly emphasizes patient self-management behaviors such as regular physical activity, restorative sleep, stress regulation, and healthful nutrition. Education is commonly used to support these aims; however, improving knowledge alone rarely produces sustained behavior change. In this Perspective, an argument will be made that effective chronic pain management requires a deliberate shift from education-focused approaches alone toward clinician-supported behavior change. Education may be necessary to reconceptualize pain and reduce perceived threat, though it is insufficient to help patients consistently adopt and sustain health-promoting behaviors in the context of pain. Drawing on pain science, health behavior change theory, and behavioral medicine, behavior change will be distinguished from education, and practical techniques will be outlined that clinicians can use to support patients in translating knowledge into action. Key principles include tailoring interventions to a patient’s stage of change, fostering self-efficacy through graded mastery experiences, using motivational interviewing to elicit values-based motivation and address ambivalence, and employing collaborative goal setting and action planning. The role of action planning, graded tasks, and motivational interviewing approaches to sustain behavior change will be emphasized. This paper will provide a clinician-focused roadmap for supporting behavior change in pain care. By moving beyond education toward intentional behavior change support, clinicians can better foster resilience, functional recovery, and sustainable self-management among individuals living with chronic pain.